CRYSTALLIZATION KINETICS OF ANDALUSITE AND SILLIMANITE DURING THE KYANITE → ANDALUSITE, KYANITE → SILLIMANITE, AND ANDALUSITE → SILLIMANITE TRANSITIONS - Ostapenko G.T. (My University, 2004)
Experimental data indicate that the general mechanism of Al 2SiO5 polymorph transitions is the dissolution of the unstable phase in an aqueous solution and the crystallization of the stable phase from it. The example of the kyanite → andalusite, kyanite → sillimanite, and andalusite → sillimanite transitions (at the nearby location of grains of these polymorphs) is employed to demonstrate that the limiting factors of these processes are the rates of surface crystallization reactions of andalusite and sillimanite. The latter are of obvious anisotropic character: the faces perpendicular and parallel to the c axis are characterized by growth according to the normal (with high rates) and layer-by-layer (low rates) mechanisms, respectively, as follows from the different types of the microtopography of these faces. The dissolution rates of andalusite and sillimanite at the rough {001} faces in water are considered, with regard for data on the solubility in water, from the viewpoint of the activated complex theory. This complex is provisionally visualized as the Al2SiO5 crystal-chemical molecule at a kink with significantly weakened Si-O and Al-O bonds. The results can be used in the analysis of mineral transformations during metamorphism.